KAJIAN PROFETIK TOKOH DAN KEARIFAN BUDAYA LOKAL NOVEL KEMBARA RINDU KARYA HABIBURRAHMAN EL SHIRAZY - Handayani, Wulan (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2023)
This study describes (1) the prophetic values of the characters in the novel Kembara Rindu by Habiburrahman El Shirazy as a source of character education, (2) the relevance of local cultural wisdom values to the prophetic characters in the novel Kembara Rindu by Habiburrahman El Shirazy. The method in this study is descriptive qualitative with content analysis, where the data obtained is the result of analysis of words, sentences and paragraphs. The data sources in this study were the text of the novel Kembara Rindu by Habiburrahman El Shirazy and books related to relevant research. The literature, listening and note-taking technique is a research technique used in data analysis related to the study of prophetic characters (transcendence, humanism and liberation) presented in the novel, which are then linked to the life philosophy of the people of Lampung as a legacy of the local cultural wisdom of the local community. The results of the analysis and discussion of the data state that the main character in the novel Kembara Rindu by Habiburrahman El Shirazy shows prophetic characters: Transcendence; Humanization; Liberation, in describing the behavior of daily life and in relation to social life. The novel Kembara Rindu by Habiburrahman El Shirazy is very closely related to the philosophy of life of the people of Lampung, namely Pi'il Pesenggiri (Have Self-Respect), Sekai Sambayan (Please Help), Nemui Nyimah (Generous), Nengah Nyappur (Open), and Bejuluk Beadek (Title Indigenous).